1991
DOI: 10.1016/1044-0305(91)80001-n
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation spectroscopy of gas-phase ferrocene cation

Abstract: The optical absorption spectrum of gas-phase ferrocene cation was measured by photodissociation (PO) spectroscopy between 570 nm and 643 nm. The PO process was loss of a cyclopentadienyl ring from the parent cation. Some structure was observed in the PO spectrum, with the highest PO being at 603 nm. The peak spacing did not correspond to a vibrational progression in the expected totally symmetric vibrational mode, and a possible assignment of the three apparent maxima involving electronic transitions from low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In any event, the 2 A 1g and 2 E 1g states are certainly close in energy and it is reasonable that the blue transition of ferrocenium (625 nm in dichloromethane) observed at room temperature could be an unresolved combination of 2 E 1u ← 2 A 1g and 2 E 1u ← 2 E 1g • transitions. 21 Moreover, the degeneracy of the E states is split by spin−orbit coupling and a low-symmetry distortion into a doublet, the extent of such splitting being different for 2 E 1u and 2 E 1g . All of these facts, together with the vibrational structure, confer a characteristic asymmetrical shape to the ferrocenium blue band.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In any event, the 2 A 1g and 2 E 1g states are certainly close in energy and it is reasonable that the blue transition of ferrocenium (625 nm in dichloromethane) observed at room temperature could be an unresolved combination of 2 E 1u ← 2 A 1g and 2 E 1u ← 2 E 1g • transitions. 21 Moreover, the degeneracy of the E states is split by spin−orbit coupling and a low-symmetry distortion into a doublet, the extent of such splitting being different for 2 E 1u and 2 E 1g . All of these facts, together with the vibrational structure, confer a characteristic asymmetrical shape to the ferrocenium blue band.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18 Evidently, we can use shorter-duration pulses 19 and/or pulses at a suitable wavelength 20 that is off-resonant with the molecular cation radicals to avoid fragmentation. The photo-dissociation 21 of FeCp 2…”
Section: +mentioning
confidence: 99%
“…Theoretical studies , on FeCp 2 + have revealed that the transition observed in the visible range is due to electronic excitation to the 2 E 1u state. The 2 E 1u ← X 2 E 2g transition was studied in the gas phase by photodissociation spectroscopy; however, the resolution was poor, and the vibrational structure was not observed . Photoelectron studies on ferrocene give some insight on the energetics of the ground and several excited electronic states of its cation. , …”
Section: Introductionmentioning
confidence: 99%